A mulher nos discursos do Presidente da República de Moçambique Armando Guebuza: o homem, o sujeito, e a mulher, seu tradicional objeto - Lúcio Dionísio Pitoca Posse (Revista Crítica de Ciências Sociais)
The narratives surrounding the struggle for gender equality and the emancipation of women in Mozambique have been central to shaping the discourses and practices of the political elite, especially when referring to the nation-state building process, beginning with the period marked by the struggle for national liberation. This aspect is observed in the speeches made by Armando Guebuza as a member of the political elite during his time as President (2005-2009 and 2010-2014), and the paper employs discourse analysis to study these speeches. The findings suggest that although Armando Guebuza came across as an advocate and promoter of gender equality and women’s emancipation in his speeches, he limited the scope of women to actions favoring the family (performing maternal and domestic tasks) and replicated the idea that women are inferior to men. This is a reflection of practices that date back to the time of the struggle for national liberation.